(untitled) (Research, Society and Development, 2021)
This study aimed to identify the main factors that affect the occupational health of nursing workers that trigger depression and point out strategies that can be used to deal with occupational stress, thus avoiding depression. Bibliographic research, exploratory, descriptive, with a qualitative approach, having as theoretical support the Theory of Basic Human Needs by Maslow (1954). The survey of articles was carried out in the Virtual Health Library (VHL) in the following databases: Lilacs, BDENF, Medline, Psychology Index – Technical-Scientific Periodicals and Virtual Campus of Public Health Brazil. The descriptors used were: “occupational health”, “nursing” and “depression”, crossed with each other. 10 articles were selected between the years 2002 to 2018. The research results showed that nursing workers can develop signs and symptoms of psychological, emotional and behavioral changes, and also often use over-the-counter psychotropic medications and medical follow-up. Strategies that can help control these symptoms are personnel management, support from leaders, meetings to expose daily difficulties, request for an occupational medicine assessment, and use of Maslow’s theory of basic human needs to help identify problems. It was concluded that depression is a mental illness characterized by chemical imbalance in brain cells and significantly affects the quality of life at work of nursing team members; thus, the leaders of the nursing teams must be aware of signs of physical and psychological illness in their workers, in order to help them.